Learning objectives in Moral Education and pupils’ behavior - Calvin, Bipoupout Jean; Lum, Muluh Rinkline (IJRDO- Journal of Educational Research, 2018)
This study is aimed at investigating the relationship between learning objectives in moral education in and pupils’ behaviour. The hypothesis which guided this study was the following: ‘there is a relationship between learning objectives related to moral education and pupils’ behaviour’. Through a survey design where 50 teachers randomly selected from 11 schools in Santa sub-division, the findings revealed that the correlation between this main variable (learning objectives and pupils’ behaviour was significant. The study revealed also that if most pupils showed a disruptive behaviour, it was because most teachers lacked skills and did not involve children in activities that permitted them to develop life skills.